2011
DOI: 10.1136/gut.2010.225011
|View full text |Cite
|
Sign up to set email alerts
|

Blood lipid and lipoprotein concentrations and colorectal cancer risk in the European Prospective Investigation into Cancer and Nutrition

Abstract: These findings show that high concentrations of serum HDL are associated with a decreased risk of colon cancer. The mechanism behind this association needs further elucidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
198
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(212 citation statements)
references
References 43 publications
11
198
3
Order By: Relevance
“…Nine studies were conducted in the USA (16,18,20,32,35,(37)(38)(39)(40) , one in Sweden (42) , five in Korea (6,9,10,22,27) , two in China (23,30) , eight in Japan (8,24,26,28,29,31,36,43) , one in Austria (41) and three in European countries (4,17,34) (Tables 1 and 2). Pooled analysis showed a significant association between serum TAG and CRN (n 29 studies; summary RR = 1·08; 95 % CI 1·05, 1·12, P < 0·00001; Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies were conducted in the USA (16,18,20,32,35,(37)(38)(39)(40) , one in Sweden (42) , five in Korea (6,9,10,22,27) , two in China (23,30) , eight in Japan (8,24,26,28,29,31,36,43) , one in Austria (41) and three in European countries (4,17,34) (Tables 1 and 2). Pooled analysis showed a significant association between serum TAG and CRN (n 29 studies; summary RR = 1·08; 95 % CI 1·05, 1·12, P < 0·00001; Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Overall analyses on the association of serum lipids and colorectal cancer Eight publications in the present meta-analysis on TC (four cohort and four case-control studies) and risk of CRC were published between 1992 and 2012 and involved a total of 10 979 CRC cases (Table 1) (4,21,22,25,34,38,42,43) . One study (1992) (38) , USA (2011) (17) , (32) , USA (43) , Japan (2010) (26) , Japan was conducted in the USA (38) , one in Sweden (42) , one in Korea (22) , two in Japan (25,43) , one in Finland (21) and two in European countries (4,34) (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Special interest has been recently focused on HDL in cancer patients. Several epidemiological studies have shown that low HDL-C level may be a risk and/or prognostic factor of biliary tract cancers (Andreotti et al 2008), prostate cancer (Mondul et al 2011;Kotani et al 2013), colon cancer (van Duijnhoven et al 2011), breast cancer (Furberg et al 2005, Melvin et al 2012) and gastric cancer (Tamura et al 2012), but not that of endometrial cancer (Cust et al 2007;Esposito et al 2014) or rectal cancer (van Duijnhoven et al 2011). Confounding factors related to obesity and metabolic syndrome may be more strongly associated with the latter cancer types (Kotani et al 2013).…”
Section: Hdl Cholesterol As a Risk Factor For Other Diseasesmentioning
confidence: 99%